Árboles para Bucaramanga (REVISTA NODO, 2007)
This article is part of an ongoing research called Strengthening of the Ecological Principal Structure as of the identification and selection of species for urban tree planting, taking place in seven (7) Colombian cities: Cúcuta, Bucaramanga, Villavicencio, Palmira, Ibagué, Neiva and Popayán. Herein are the results for the city of Bucaramanga, including a brief survey of the current landscaping condition, along with the plants’ selection criteria, and the listing of chosen species to strengthen Bucaramanga’s Ecological Principal Structure (EEP, asits acronym in Spanish), using ground/soil, water, fauna, and ecosystem elements of design.
Keywords: Urban tree planting; Ecological Principal Structure; biological corridors